Evaluating the climate resilience in terms of profitability and risk for a long-term corn-soybean-wheat rotation under different treatment systems - Eeswaran, R.; Nejadhashemi, A.P.; Miller, S.R. (Elsevier, 2021)
Increasing climate variability and extreme weather events impose significant challenges to the crop production systems throughout the world. Alternative agricultural treatment systems have been proposed to manage these challenges. However, these treatments have not been sufficiently studied for their ability to improve climate resilience, especially in terms of profitability and risk management, which are important metrics of resilience that determine farm-level adaptation. Hence, we evaluated the climate resilience of three alternative agricultural treatments for a long term (27-years) rotation of corn-soybean-wheat, cast in the temperate humid climate of South west Michigan, United States. The three alternative treatments include no-till, reduced input, and US Department of Agriculture (USDA) certified organic. These are compared to the conventional treatment along with the same crop rotation. Means and volatility of expected gross margins and risk preferences were used as the evaluation metrics. Results demonstrate that the net revenues from the USDA certified organic are largely expected to exceed the net revenues of conventional treatment. Also, for all commodities, organic treatment may exert greater annual stability in revenues. The no-till treatment dominates conventional and reduced input practices in expected annual net revenues with a relatively lower risk to those revenues in light of climate extremes. Furthermore, the organic and no-till treatments showed appropriateness to cater to a range of farmers with different risk preferences. Therefore, the organic and the no-till treatments were deemed climate-resilient. The conventional and reduced input treatments did not show resilience thus will be vulnerable to the changing climate. Despite the economic support for adopting resilient practices, growers have been slow to adopt new approaches. We suggest future research needs for understanding grower motivations for adopting climate-resilient practices and consider policy implications.
Keywords: Climate extremes; Economic return; Organic agriculture; Payoff matrix; Risk; Row crops